Challenges and Practice to Educating Children with Autism Spectrum Disorders in Inclusive Classroom - Acharya, Raju (Spectrum of Humanities and Social Sciences, 2025)
The study had the main objective of to identify challenges and practice to educating the children with autism in inclusive education and explore the ways of mitigating these challenges. The study had used qualitative method which focused on interview, with parents and special education teacher, a purposeful sampling procedure was used to select two parents, two teachers and two students. The main issue to success inclusion environment for students with ASD is the concern of stakeholders to collaborate and consult with the stakeholders to workout strategies as creative planning, teamwork, building a climate of acceptance for both parents and students, along with tailored (personalized) teaching methods. Promoting the inclusion of children with autism in schools is enhanced by engaging families in activities encompassing daily living and extracurricular pursuits. Schools must also work to eliminate barriers such as stigmatization and bullying that can hinder inclusion. Creating a supportive and disability-friendly atmosphere is vital, trained paraprofessionals, and school administrators should encourage teachers to maintain positive relationships with students and their families, fostering participation in inclusive education.